Prosedur Penyandaran Kapal Kargo Mv. Serasi V di Pelabuhan Deli Belawan Pada Pt. Admiral Lines Cabang Belawan - Firdaus Waya; Dafid Ginting; Suratni Ginting (Universitas Kristen Indonesia Toraja, 2025)
Belawan Port, as one of the largest and busiest ports in Indonesia, has a strategic role in supporting economic activities, especially in terms of sending and receiving goods. As cargo volumes increase, efficiency and safety in the berthing process of cargo ships become crucial factors. This paper discusses the docking procedure for cargo ships at Belawan Port, which includes technical, administrative stages and safety aspects that must be complied with by every ship that will dock. This research uses qualitative methods with a descriptive approach. Data was collected through literature study, interviews with related parties at Belawan Port, and field observations. The research results show that limited ship draft at Belawan Port is a significant challenge that affects the port's ability to serve large ships. In addition, several operational obstacles were found such as limited facilities, congestion, and coordination between institutions. This paper also explores these various challenges and provides recommendations for increasing operational efficiency through optimizing backup procedures and adopting technology. By understanding berthing procedures in depth and adopting best practices, Belawan Port is expected to increase its competitiveness and support regional economic growth.